Increasing Nonsteroidal Anti-inflammatory Drugs and Reducing Opioids or Paracetamol in the Management of Acute Renal Colic: Based on Three-Stage Study Design of Network Meta-Analysis of Randomized Controlled Trials - Hui-Yun Gu; Jie Luo; Jun-Yi Wu; Qi-Sheng Yao; Qi-Sheng Yao; Yu-Ming Niu; Yu-Ming Niu; Chao Zhang (Frontiers Media S.A., 2019)
Background: Currently, although non-steroidal anti-inflammatory drugs (NSAIDs) were recommended for acute renal colic in the 2018 European Association of Urology guidelines, there are no specific NSAIDs and no specific routes of administration in this guideline. The clinical practice of advocating intravenous opioids as the initial analgesia is still common out of the fear of adverse events from NSAIDs.Objectives: To comprehensively assess the efficacy and safety of NSAIDs, opioids, paracetamol, and combination therapy for acute renal colic.Methods: Ovid MEDLINE, Ovid EMbase, the Cochrane Library, Clinical Trials Registry Platform for Clinicaltrials.gov, and WHO International Clinical Trials Registry Platform were searched through February 2, 2018. Two reviewers selected all randomized controlled trails (RCTs) regarding NSAIDs, opioids, paracetamol, combination therapy, and placebo were identified for analysis. We designed a three-stage strategy based on classification and pharmacological mechanisms in the first stage, routes of administration in the second stage, and specific drug branches with different routes in the third stage using network meta-analysis. The pain variance at 30 min was seen as the primary outcome.Results: 65 RCTs with 8633 participants were involved. Comparing different classification and pharmacological mechanisms, combination therapy with more adverse events was more efficient than NSAIDs for the primary outcomes. Opioids gave rise to more nonspecific adverse events and vomiting events. NSAIDs were superior to opioids, paracetamol, and combination therapy after a full consideration of all outcomes. Comparing different routes of administration, NSAIDs with IV or IM route ranked first from efficacy and safety perspective. Comparing different specific drug branches with different routes, ibuprofen via IV route, ketorolac via IV route and diclofenac via IM route were superior for the management of acute renal colic. The results from diclofenac using IM route were more than those from ibuprofen used with IV route and ketorolac with IV route.Conclusions: In patients with adequate renal function, diclofenac via the IM route is recommended for patients without risks of cardiovascular events. Ibuprofen and ketorolac with IV route potentially superior to diclofenac via IM route remain to be investigated. Combination therapy is an alternative choice for uncontrolled pain after the use of NSAIDs.